2019
DOI: 10.1093/infdis/jiz623
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clearance of Anal Human Papillomavirus (HPV)-16 and HPV-18 Infection, and Their Determinants, Among Human Immunodeficiency Virus-Infected Men Who Have Sex With Men in France

Abstract: Background Prospective data on the natural history of anal human papillomavirus (HPV) infection are scarce in human immunodeficiency virus (HIV)-infected men who have sex with men (MSM). Methods We analyzed incidence and clearance of HPV-16 and HPV-18 in a French cohort of HIV-infected MSM, aged ≥35 years, followed-up annually (n = 438, 2014–2018). Results Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
3
12
1
1
Order By: Relevance
“…More specifically, 8/10 (80%) patients with previously documented “other” HR‐HPV were negative on follow‐up; only two such patients with HR‐HPV 16/18 were identified. This correlates with previously published literature that describes HR‐HPV 16/18 is either slow to clear or does not clear 12‐14 . Further, a recent study prospectively examined the natural history of anal HPV infections and noted that HPV 16 was frequently associated with high‐grade lesions and was slow to clear 12 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…More specifically, 8/10 (80%) patients with previously documented “other” HR‐HPV were negative on follow‐up; only two such patients with HR‐HPV 16/18 were identified. This correlates with previously published literature that describes HR‐HPV 16/18 is either slow to clear or does not clear 12‐14 . Further, a recent study prospectively examined the natural history of anal HPV infections and noted that HPV 16 was frequently associated with high‐grade lesions and was slow to clear 12 .…”
Section: Discussionsupporting
confidence: 87%
“…This correlates with previously published literature that describes HR-HPV 16/18 is either slow to clear or does not clear. [12][13][14] Further, a recent study prospectively examined the natural history of anal HPV infections and noted that HPV 16 was frequently associated with high-grade lesions and was slow to clear. 12 Such data, as well as those in our study, may further identify patients at greater risk and improve triage.…”
Section: T a B L E 1 Correlation Between Asc-h And Asc-us And Hr-hpv Test Results In Comparison To Nilmmentioning
confidence: 99%
“…This finding of a relationship between HSIL-positivity and poor immunological status is consistent with previous observations that prolonged antiretroviral treatment [ 21 23 ] and a high CD4 count, regardless of CD4 nadir [ 24 ], are protective factors against HSIL. A recent prospective study observed a similar incidence of HPV-16 and -18 genotypes in the anal mucosa of French HIV+MSM, but HPV-16 was more persistent and therefore more closely correlated with the presence of HSIL [ 25 ]. In a retrospective study of “alpha-human papillomavirus” in the anal mucosa of German HIV+ patients, the presence of HSIL and simultaneous infection was associated with high- and low-risk genotypes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of dosage efficacy is not possible, as we do not collect information on the exact amount of gel used. While biannual4 46–48 and annual49–53 anal HPV sampling in longitudinal studies is common, that length of follow-up will not give sufficient detail to evaluate the study’s objectives. In an ideal research setting, HPV status would be ascertained daily to have a more precise measurement of the time of HPV acquisition; however, to minimise burden on the patient, the current schedule was deemed optimal.…”
Section: Discussionmentioning
confidence: 99%